Revisiting the spiral of silence in a social media environment: Egypt’s 2014 presidential election as a case study - Elshahed, Heba T. Saleh (AUC Knowledge Fountain, 2014)
With the advent of the Internet and anonymous features of online media, users have established novel platforms to voice their opinion freely without fear of negative feedback. This thesis explores the application of a long-standing public opinion theory– the spiral of silence by Elizabeth Noelle-Neumann–within the prevalent Social Networking Sites (SNS), particularly Facebook. When applying spiral of silence to online mediated environment, it seems intuitive that the lack of verbal cues and anonymity offered would serve to undermine the fear of isolation and restlessness that results in unwillingness to express minority views. This research contributes to understanding how the spiral of silence might operate in the social media era, and adds a view on how SNS influence opinion-forming variables. This study uses survey and in-depth interviews to assess willingness to speak out on political stands during the Egyptian presidential election of 2014. A survey was distributed to query Egyptian SNS users about their willingness to express their political opinion prior to casting votes in the nation’s 2014 presidential election. In-depth interviews were also conducted offering interpretations to the perception of the general opinion climate, and expected consequences of expressing views about controversial issues to Facebook's friends. This study considered online negative feedback on the users' profile as the form of fear of isolation, to accommodate new form of isolation in social media environment. Tests of negative evaluation fears showed no relation between sample's apprehension of a negative feedback on facebook and their tendency to express their political opinion on the presidential election, questioning spiral of silence's explanation of compelling social factors. Respondents with higher knowledge level showed higher tendency to express their views on the issue of the election than those with lower knowledge level regardless of their social belonging status. The perceived majority's opinion showed no influence on users' inclination to express views, nor did it influence willingness to enter a discussion with holders of opposing views. Willingness to speak out under a minority label was not affected in an online environment. Moreover, no statistical significance was found to indicate that spiral of silence existence is still embedded in a real-life setting. Contrary to literature on the spiral of silence, findings revealed equal attention paid to elements of close circle and community at large, and perceived importance of identifying their opinion on the presidential election prior to evaluating personal opinion. The author can be contacted at hebaelshahed@aucegypt.edu,